Concentrations and characteristics of amphibole fibres in the lungs of workers exposed to crocidolite in the British gas-mask factories, and elsewhere, during the second world war. Issue 1 (February 1982) - Morgan, A; Holmes, A
Abstract : Concentrations and length distributions of uncoated and coated amphibole fibres in the lungs of 27 workers at the Leyland, Nottingham, and Blackburn gas-mask factories were measured after death with the light microscope using the membrane filter technique. Measurements were also made on a worker exposed to crocidolite at the Chemical Defence Experimental Establishment, Porton, and on three miners from the Wittenoom mine in Western Australia where the crocidolite used in the manufacture of military respirators is reputed to have originated. In selected cases, fibre concentrations and dimensions were also measured with the electron microscope. All but two subjects died with a mesothelial tumour. Fibre concentrations ranged from 7 x 10(4) to almost 10(9) fibres/g dry weight. There appeared to be no relation between latent period and fibre concentration. The significance of the wide range of fibre concentrations which was associated with the development of mesothelial tumours is discussed and also the relation between the relative frequency and dimensions of uncoated and coated fibres.